2021
DOI: 10.1161/strokeaha.120.031742
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Biology and Stroke

Abstract: Circadian biology modulates almost all aspects of mammalian physiology, disease, and response to therapies. Emerging data suggest that circadian biology may significantly affect the mechanisms of susceptibility, injury, recovery, and the response to therapy in stroke. In this review/perspective, we survey the accumulating literature and attempt to connect molecular, cellular, and physiological pathways in circadian biology to clinical consequences in stroke. Accounting for the complex and multifactorial effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 129 publications
1
57
0
Order By: Relevance
“… 26 Thus, it is crucial to incorporate the circadian dimension into stroke research and therapy design. 4 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“… 26 Thus, it is crucial to incorporate the circadian dimension into stroke research and therapy design. 4 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to HPA's neurohormonal role, host circadian rhythm also affects MGBA at steady state and in response to stroke. 95 For example, a study using circadian mutant Clock ∆19/∆19 gene knockout mice revealed that a functional circadian signaling is required for the beneficial effects of the gut microbiota on recovery after myocardial infarction 96 ; however, this has not yet been examined in models of stroke.…”
Section: Systemic Circulation (Hormones Cytokines and Metabolites)mentioning
confidence: 99%
“…There are very few reports of REVERB therapies in neurological preclinical or clinical studies; yet, recent interest in the circadian regulation of disease is taking shape. Stroke infarct size has significant circadian variability and is now under great scrutiny for improving outcomes and secondary prevention of injury ( Lo et al, 2021 ).…”
Section: Clock Genes As Targets In Subarachnoid Hemorrhagementioning
confidence: 99%